Kiwi circle : a social platform connecting Chinese international students with local New Zealanders : a thesis submitted in partial fulfilment for the degree of Master of Design, Massey University, Wellington, New Zealand - Yu, Liang (Massey University, 2019)
In the past 25 years, international education has grown to become New Zealand’s fourth largest export industry, generating around 5.1 billion dollars to its economy (New Zealand Education, 2018). While Chinese students comprise the largest proportion of consumers within this sector, research indicates that Chinese international students in New Zealand are less satisfied than students from all other countries. This research proposes to design an online social platform to facilitate connections between these Chinese international students and local New Zealanders, in order to assist them in adjusting to studying and living in New Zealand. Furthermore, the platform would provide a channel for local New Zealanders who are interested in the Chinese culture to learn about and interact with it through contact with Chinese students. This research project aims to add value to New Zealand’s international education industry, by improving the overall quality of international students’ experience.
Some Figures may be copyrighted but they have not been removed for the sake of clarity.
Keywords: Online social networks; Planning; Design; Social interaction; Chinese students; New Zealand; Interpersonal communication; Cross-cultural studies